Percepção, memória e reação emocional de pacientes com esclerose múltipla - Fuso, Simone Freitas [UNIFESP] (2008)
Multiple sclerosis (MS) is a chronic inflammatory and autoimmune disease that causes multilesions in the central nervous system (CNS). These lesions may result in cognitive deficits, mainly in the explicit episodic memory. On the other hand, a high prevalence of emotional disorder in MS has been reported. It is widely known that the emotional information processing involves the functioning of many regions of the CNS. However, few studies investigated the processing of emotion in MS. In this way, the aim of this study was to evaluate the perception, the memory and the reaction of MS patients in the presence of affective charge and neutral stimuli. Within this scope, 20 high arousal unpleasant figures and 20 neutral figures from the International Affective Picture System were presented to both 21 volunteers (MS patients) and 21 healthy individuals. A subjective perception task of the pictures was performed and the physiologic measures of skin conductance and heart rate were recorded, which were followed by the free recall and recognition memory tasks. The results adduced that MS patients display an appropriate emotional perception. Concerning memory, it was observed that the patients recalled a lower number of figures than the control group and did not display an increment in recalling the unpleasant figures. Nevertheless, they recalled better the high arousal figures than the neutral figures. With reference to the recognition memory, the patients did not suffer any impairment, although they have reacted slower to the emotional figures. In terms of emotional reaction, it was perceived a similar average variation in the skin conductance between those two groups. Referring to the heart rate, the patients displayed a similar bradycardia in the presence of the unpleasant and neutral figures, in contrast to the control group, which displayed a greater bradycardia in the presence of the former figures. Moreover, it was noticed an habituation failure in the physiological responses in the presence of the emotional stimuli, in comparison with the responses to the initial and final figures compiled by the test. The results suggested that the automatic mechanisms, activated by the arousal and mediated by the functioning of the amygdala, are preserved in MS, while there is a damage seen in the processing of the affective valence of the stimuli, involving the cognitive and cortical processes. Therefore, it is concluded that, despite the fact that the subjective perception is preserved in MS, the free recall of the unpleasant figures remains impaired, as well as the emotional reaction in their presence. Finally, it is suggested that the impairment that affects the processing of the emotional stimuli may make the MS patients more susceptible to both affective and mood disturbance and, in addition to cognitive deficits, influences the quality of life of these patients.